Bioethical principles and health-care services users’ rights - Carla Spiri, Wilza; Wey Berti, Heloísa; Duarte Pereira, Maria Lúcia (O Mundo da Saúde, 2006)
In health services, especially in a hospital setting, the habit of using a terminology rich in complicated vocabulary with neologisms and jargon typical of the hospital setting is very common in the communication between professionals and patients, guar- dians and relatives and in many cases reflect intentions of exercising power and dominion. Health professionals, imbued with the capacity of curing, have special prestige and status which if denied may lead to a power abuse, characterized by threat sensations when their opinions are questioned and by unilateral decisions on what is considered best for the patient, without a broader discussion about the patient’s conditions and options. Nursing, as part of the health-care system, has an important role on reflecting about these questions, aiming to grant to all health-service users the guarantee of an equitable care providing. Based on these reflections, the proposal of the present study is to analyze the law on health-service users’ rights and health policies in São Paulo State, as well as aspects of ethical questions like autonomy, beneficence, justice, respect for liberty and for the value of human life.